2015
DOI: 10.1002/ppul.23217
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for lung function decline in a large cohort of young cystic fibrosis patients

Abstract: Objective To identify novel risk factors and corroborate previously identified risk factors for mean annual decline in FEV1 percent predicted in a large, contemporary, U.S. cohort of young cystic fibrosis patients. Methods Retrospective observational study of participants in the EPIC Observational Study, who were Pseudomonas–negative and ≤12 years of age at enrollment in 2004-2006. The associations between potential demographic, clinical and environmental risk factors evaluated during the baseline year and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
1
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(101 citation statements)
references
References 32 publications
4
93
1
3
Order By: Relevance
“…First, our inclusion and exclusion criteria selected a sub-group of CF patients, which do not reflect the entire CF population. However, lung function data of our patients were comparable to other studies [27,41]. Our data should thus provide meaningful results for the general CF population.…”
Section: Discussionsupporting
confidence: 87%
“…First, our inclusion and exclusion criteria selected a sub-group of CF patients, which do not reflect the entire CF population. However, lung function data of our patients were comparable to other studies [27,41]. Our data should thus provide meaningful results for the general CF population.…”
Section: Discussionsupporting
confidence: 87%
“…This increased annual decline of 0.63 exceeds our finding of 0.35 in our overall model and 0.47 in our sensitivity analysis. However, it is difficult to compare magnitude given that Cogen et al conducted a between subject analysis in contrast to our within subject analysis.…”
Section: Discussionmentioning
confidence: 88%
“…The effect of S. maltophilia infection on lung function decline and other respiratory outcomes in CF is unclear . While older studies have not shown an effect on respiratory outcomes, there is emerging evidence that S. maltophilia is associated with increased risk of pulmonary exacerbations and possibly even acceleration of lung function decline …”
Section: Introductionmentioning
confidence: 99%
“…In addition to the high prevalence of S. aureus among children, pediatric CF studies have provided further reason to worry: S. aureus has been associated with higher airway inflammation 25,26 , lower lung function 27,28 , and even higher subsequent mortality when detected together with P. aeruginosa 29 . Further, these associations were for all S. aureus ; as described below, specific subtypes of S. aureus (such as MRSA and small-colony variants of S. aureus (SCVs)) may be associated with even worse outcomes than other S. aureus .…”
Section: Cf Microbiologymentioning
confidence: 99%